Enablers and Roadblocks for Green Cosmetics Entrepreneurs in India: An Exploratory Study - Upadhyaya, Abhilasha Singh; Sijoria, Charu (AMC Indian Journal of Entrepreneurship, 2024)
Purpose : The present study aimed to investigate the perspectives of recent entrepreneurs operating in the green cosmetics industry. This study also aimed to identify any potential barriers to these entrepreneurial endeavours as well as the factors that contribute to their success. Methodology : Three companies were taken into consideration for this case-study-based study. These businesses are more likely to have teething issues because they have been in the green cosmetics industry for fewer than five years. The workings of these companies, the factors that impact their operation, and the problems they encounter have all been investigated through management interviews. Additionally, business canvasses have been made for these companies. Findings : The study’s findings demonstrated that psychological and personal factors, like environmental consciousness and concern, play a significant role in influencing customers’ evolving views on buying green cosmetics. Customers who are more concerned with maintaining a healthy lifestyle are the potential market for these products. The quality of the substances used in the manufacture of products has a considerable impact, but consumers primarily base their final purchasing decisions on their feelings. Practical Implications : It was advised that businesses inform both current and potential customers about the quality of the substances used in the production of their goods. Marketers must focus on spreading awareness of the content because consumers are extremely selective and cautious about the quality of the green items they use. Since consumers’ decisions about green cosmetics have been found to be heavily impacted by their emotions, marketing materials must be developed with these feelings and emotions in mind. Although this study has limitations, by incorporating more entrepreneurs in the wellness and green cosmetics businesses, it does offer prospects for further research. Originality : The current research effort aimed to portray the story from the perspective of green cosmetics businesses, as there is an absence of literature that offers an alternative perspective to that of green buyers. The study’s choice of entrepreneurs is particularly distinctive as all three of the enterprises it examined had been in operation for less than 5 years.